Trainee social justice advocacy: investigating the roles of training factors and multicultural competence. Issue 2 (3rd April 2019) - Presseau, Candice; Luu, Linh P.; Inman, Arpana G.; DeBlaere, Cirleen
Abstract: Theoretical research asserts that social justice advocacy (SJA) represents an extension of multicultural competence (MC). However, limited empirical literature examines if and how SJA manifests and is developed as an aspect of trainee MC. The current study used path modeling to examine direct and indirect links between aspects of training environment and trainee MC and SJA for a sample of 197 trainees embedded in counseling-oriented training programs. MC demonstrated the strongest positive association with SJA. In addition, multicultural training environment, but not social justice training environment, influenced SJA indirectly through MC. Results are encouraging of a differentiation between multicultural and social justice training emphases, with practical implications for training programs seeking to enhance and foster both MC and SJA among their trainees.